2014
DOI: 10.1007/s00603-014-0568-y
|View full text |Cite
|
Sign up to set email alerts
|

On the Occurrence of Anhydrite in the Sulphatic Claystones of the Gypsum Keuper

Abstract: We investigate why the sulphatic claystones of the Gypsum Keuper contain anhydrite rather than gypsum even at small depths of cover. This question is relevant due to the phenomenon of swelling of anhydritic claystones, which is attributed to the transformation of anhydrite into gypsum and has caused serious damage to a number of tunnels. In tunnelling, the Gypsum Keuper formation is crossed at rather small depths, where simplified thermodynamic considerations indicate that the calcium sulphate should be encoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Dissolved salts and minerals other than calcium sulfate modify the saturation concentrations of gypsum and anhydrite. Recent contributions on this topic (Serafeimidis & Anagnostou, 2013Anagnostou et al, 2015) report the effect of the solute mineralogical content on gypsum or anhydrite equilibrium concentrations.…”
Section: Rock Damagementioning
confidence: 99%
“…Dissolved salts and minerals other than calcium sulfate modify the saturation concentrations of gypsum and anhydrite. Recent contributions on this topic (Serafeimidis & Anagnostou, 2013Anagnostou et al, 2015) report the effect of the solute mineralogical content on gypsum or anhydrite equilibrium concentrations.…”
Section: Rock Damagementioning
confidence: 99%
“…As discussed, e.g., by Anagnostou et al (2014), a low activity W a of the pore water can inhibit AGT. The water activity is defined as the ratio between the partial evaporation pressure in the vicinity of the pore (p D ) to the saturated evaporation pressure over dilute water (p S ).…”
Section: Influence Of the Activity And Pore Water Potentialmentioning
confidence: 92%
“…They found the solubility of gypsum to increase in the presence of clays and in the case of small pores. Anagnostou et al (2014) then investigated, why anhydrite rather than gypsum is found at small depths of cover, which is usually the case in tunneling and came to the conclusion that the clay minerals and thus the low water activity are most likely responsible for the anhydrite to be the thermodynamically stable phase, rather than gypsum, thus preventing AGT prior to the excavation of tunnels. They used thermodynamic computations to determine the crystallization pressure of gypsum and found that the pressures are considerably lower in the case of low water activities (Serafeimidis and Anagnostou, 2014a).…”
Section: Modelling Of Anhydritic Swelling Claystones -Theoretical Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies focused mainly on the formation of natural mineral deposits and applications in the building industry, that is, for gypsum targeting and mining. More recent work, however, has investigated the reaction kinetics as well as the critical geochemical conditions (Anagnostou et al, ; Serafeimidis & Anagnostou, ), including the effect of regional groundwater flow and hydrological boundary conditions, that impact the swelling of clay‐sulfate rocks (Butscher, Huggenberger et al, ; Butscher, Huggenberger, Einstein et al, ). Furthermore, several numerical models have been proposed, including models that couple hydrological, chemical, and mechanical processes, to simulate the swelling of such rocks.…”
Section: Introductionmentioning
confidence: 99%